2020
DOI: 10.3390/genes11060631
|View full text |Cite
|
Sign up to set email alerts
|

Gill Transcriptome Sequencing and De Novo Annotation of Acanthogobius ommaturus in Response to Salinity Stress

Abstract: Acanthogobius ommaturus is a euryhaline fish widely distributed in coastal, bay and estuarine areas, showing a strong tolerance to salinity. In order to understand the mechanism of adaptation to salinity stress, RNA-seq was used to compare the transcriptome responses of Acanthogobius ommaturus to the changes of salinity. Four salinity gradients, 0 psu, 15 psu (control), 30 psu and 45 psu were set to conduct the experiment. In total, 131,225 unigenes were obtained from the gill tissue of A. ommaturus using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
5
9
0
Order By: Relevance
“…Blood and water in gills are separated by just a few micrometers, thus facilitating the exchange of gases and allowing gill tissue to be exposed to environmental variation and pollutants [19]. Moreover, gills can balance the ion concentration in blood and acid base in freshwater and seawater-adapted fish [20][21][22]. Salinity changes can cause many lesions in gills, such as vascular congestion [8], lamellar fusion, mucosal cell and gill filament epithelium hyperplasia, loss of the structural integrity of pillar cells, and an increased number of chloride cells [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Blood and water in gills are separated by just a few micrometers, thus facilitating the exchange of gases and allowing gill tissue to be exposed to environmental variation and pollutants [19]. Moreover, gills can balance the ion concentration in blood and acid base in freshwater and seawater-adapted fish [20][21][22]. Salinity changes can cause many lesions in gills, such as vascular congestion [8], lamellar fusion, mucosal cell and gill filament epithelium hyperplasia, loss of the structural integrity of pillar cells, and an increased number of chloride cells [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transcriptome analysis of cobia ( Rachycentron canadum ) under salinity stress showed that metabolism was the pathway that was the most affected by salinity changes [ 22 ]. Sun et al found that the DEGs related to the adaptive regulation mechanism of salinity in Acanthogobius ommaturus were mainly involved in the metabolic, ion transport, and signal transduction processes [ 23 ]. Several genes of the solute carrier (SLC) gene family have been identified as candidate genes that mediate the response of the tiger puffer ( Takifugu rubripes ) to low-salinity stress [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of DEGs in the FG vs. SG groups at the three growth stages was determined using edgeR package (Robinson et al, 2009). All the unigenes were annotated on NCBI nonredundant protein (NR), eukaryotic orthologous group (KOG), Kyoto Encyclopedia of Genes and Genomes (KEGG), NCBI nucleotide (NT), gene ontology (GO) and Swiss-Prot protein databases (Conesa et al, 2005;Kanehisa et al, 2008;Sun et al, 2020).…”
Section: Library Preparation and Rna-seq Analysismentioning
confidence: 99%